S20 CRTH2 is expressed by the bronchial epithelium and its activation drives epithelial differentiation. (14th November 2013) - Stinson, SE; Amrani, Y; Carlsson, M; Brightling, C
Abstract : Background: The chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTh2) is implicated in the pathogenesis of asthma, but its expression in the bronchial epithelium and potential role in airway remodelling is unknown. Methods: CRTh2 protein expression was assessed in bronchial biopsies (n = 24) and primary epithelial cells (n = 16) using immunohistochemistry, and using flow cytometry, immunofluorescence, and quantitative RT-PCR (QT-PCR) respectively. The effects of 13, 14-dihydro-15-keto Prostaglandin D2 (DK-PGD2) on epithelial cell migration and differentiation was determined. Results: The number of submucosal CRTh2 positive inflammatory cells was increased in asthma compared to healthy controls 27.57 per mm 2 sub-mucosal area (9.82) versus 48.17 (14.04) (p = 0.0049). CRTh2 expression was identified on normal and asthmatic epithelial cells, but its expression was decreased in bronchial biopsies from asthmatics 21.43 per 10mm 2 epithelial area (7.85) versus healthy controls 62.34 (36.41) (p = 0.0071) and similar findings were observed in primary epithelial cells. Squamous metaplasia of the bronchial epithelium was increased in asthma and related to decreased CRTh2 expression. DK-PGD2 promoted epithelial cell migration 12-fold increase (p = <0.0001) and in air-liquid interface cultures increased the number of MUC5AC + and involucrin + cells, which were blocked with a CRTh2 specific antagonist. Conclusions: CRTh2 is expressed by the bronchial epithelium and its activation drives epithelial differentiation suggesting that in addition to its well characterised role on inflammatory cell migration CRTh2 might contribute to airway remodelling in asthma.